(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2024)
The contribution aims to investigate the influence of Max Scheler’s Wesen und Formen der Sympathie on Ernesto De Martino’s thought, during the elaboration period of Il mondo magico’s theoretical framework. The paper claims that De Martino’s approach to Scheler’s phenomenology can be included among the conditions of possibility of the Italian philosopher’s detachment from idealism and of the formulation of his original epistemological stance. Within this framework, tracing Sympathiebuch’s line of influence on De Martino would make possible to read the problem of the experience of magic from a phenomenological standpoint. In the first section, the paper provides an outline of the philosophical and cultural environment in which De Martino came into contact with phenomenology and, specifically, with Scheler’s philosophy. In the second section, the paper presents the features of Scheler’s philosophy that would influence De Martino’s thougt in the first half of the 1940s. To this purpose, the contribution takes into account Sympathiebuch’s main conceptual cores, taking as its guiding thread the definition of the phenomenological concept of Mit-fühlen and the possibility to extend its potentialities to an ethnological project. In the third section, the paper presents an interpretation of Il mondo magico in the light of Scheler’s categories, highlighting the argumentative junctures in which the phenomenological conceptual toolkit seems to be most effectively employed by De Martino in the study of magic and ritual phenomenona.